Letter from L. Poulson Dobson to James Curtis Booth - Dobson, L. Poulson (1870)
L. Poulson Dobson, corresponding secretary for the Society of the Alumni for the University of Pennsylvania invites James Curtis Booth (1810-1888) to deliver an address to the Society. Booth notes that he has declined the request due to lack of time.
Keywords: Booth, James Curtis, 1810-1888; University of Pennsylvania. Society of the Alumni